2016
DOI: 10.1038/srep25709
|View full text |Cite
|
Sign up to set email alerts
|

Minicollagen cysteine-rich domains encode distinct modes of polymerization to form stable nematocyst capsules

Abstract: The stinging capsules of cnidarians, nematocysts, function as harpoon-like organelles with unusual biomechanical properties. The nanosecond discharge of the nematocyst requires a dense protein network of the capsule structure withstanding an internal pressure of up to 150 bar. Main components of the capsule are short collagens, so-called minicollagens, that form extended polymers by disulfide reshuffling of their cysteine-rich domains (CRDs). Although CRDs have identical cysteine patterns, they exhibit differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…Interestingly, CRDs also characterize minicollagens and other important structural nematocyst proteins [ 11 , 31 – 33 ]. Specifically, the CRDs of minicollagens are known to polymerize to form the basic scaffold of the nematocyst capsule [ 32 , 34 , 35 ]. A signal peptide was identified for all sequences that were not truncated at their 5’end.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, CRDs also characterize minicollagens and other important structural nematocyst proteins [ 11 , 31 – 33 ]. Specifically, the CRDs of minicollagens are known to polymerize to form the basic scaffold of the nematocyst capsule [ 32 , 34 , 35 ]. A signal peptide was identified for all sequences that were not truncated at their 5’end.…”
Section: Resultsmentioning
confidence: 99%
“…The CRDs are present in numerous proteins involved in nematocyst biosynthesis and function (Ozbek et al, 2009;Balasubramanian et al, 2012). Recently, it was shown that the CRDs facilitate multimerization of proteins through direct interaction with each other, and that certain CRD sequences enable a higher interaction valency than others (Tursch et al, 2016). The dynamic nature of the CRD disulfide bonds has been demonstrated in the creation of re-codable surfaces where surface chemistry of a substrate can be written and re-written using the reversible nature of the CRD disulfide bonds (Gegenhuber et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The CRDs are proposed to perform two functions in the creation of nematocyst structures. First, they function as multimerization domains that control organization and self-assembly of higher order protein complexes (Meier et al, 2007;Tursch et al, 2016). Second, they contain stored intrachain disulfide bonds that are mobilized at the right time to create interchain crosslinks that stabilize the protein complexes (Meier et al, 2007;Beckmann et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the structural elements responsible for their distinct structures were analyzed to gain possible information about the mechanisms of mini-collagen disulfide rearrangement in their assembly into polymeric fibers. With better information on this process, mini-collagens containing functional domains of type I and IV collagens could be used for the preparation of mechanically highly resistant frameworks for cell adhesion and thus constitute promising innovative biomaterials [34]. However, their architecture is also of interest when nematocyts in various intact nematocytes are tested concerning its diagnostic feasibility when coming into contact with sialic acid coated surfaces.…”
Section: Introductionmentioning
confidence: 99%